POLYPEPTIDE MAPPING AND WESTERN BLOT ANALYSIS OF MYCOPLASMA GALLISEPTICUM FIELD ISOLATES - M. Rauf; Z. I. Chaudhary; M. Younus; A. A. Anjum; H. M. Khan; M. A. Ali (Journal of Animal and Plant Sciences, 2014)
Mycoplasma gallisepticum (MG), an intracellular bacterium, causative agent of chronic respiratory disease (CRD) of poultry, is transmitted vertically and horizontally. MG is cosmopolitan in distribution and causes huge economic losses to poultry industry. To lower economic losses and spread of bacteria, molecular characterization can provide basis for its control. Field isolates of MG prevalent in Pakistan were characterized to check antigenic variations and determination of immunogenic proteins. Protein profiling was carried out using Sodium Dodecyl Sulphate Poly Acrylamide Gel Electrophoresis (SDS-PAGE) using 12.5 percent resolving gel under reduced conditions. Determination of immunogenic antigens among segregated proteins was done by western blotting. Five major polypeptides with molecular weights of 32.35, 43.65, 52.48, 64.56 and 70.8kDa were revealed. No antigenic variation was observed by SDS-PAGE among isolated bacteria from out breaks of CRD. Out of five polypeptides three with molecular weights of 52.48, 43.65 and 32.35kDa were declared immunogenic in nature as determined by western blotting. Results of present study can be used as base line for production and evaluation of subunit vaccines.
Keywords: Mycoplasma gallisepticum; CRD; SDS-PAGE; Polypeptide and Western blot